ASSESSMENT OF BIOCHEMICAL VARIATIONS AND SPLENOMEGALY DURING FALCIPARUM MALARIA IN MICE MODEL - M. SOWJANYA; KUMAR , K. KALYAN; K. SUNITA (The Bioscan, 2013)
The present study was carried out to determine the serum biochemical and spleen external morphological changes in Plasmodium falciparum infected and control C57BL/6J male mice. Present work reports the levels of lipid profile, AST, ALT, ALP, total bilirubin, direct bilirubin, indirect bilirubin, total protein, albumin, globulin, GGT, serum creatinine and quantification of parasites in malaria infected group. Malaria parasitemia was monitored up to day 42 by observation of blood smears of mice. The peak level of parasitemia (35% on day 11) and condition of splenomegaly was observed in falciparum infected mice in comparison with control. Liver transaminases, lipid profile and total protein had shown statistically significant changes (p < 0.05) whereas total albumin, indirect bilirubin and serum creatinine were not significantly (p > 0.05) altered. Our observations strongly support the hypothesis that falciparum malaria infection affects serum biochemical profiles and enlargement of spleen as a valuable pathological sign in animal model.